India at 70: Introduction to the BASAS 2017 Special Issue. Issue 3 (3rd July 2018) - Boni, Filippo; Maiorano, Diego
Abstract : This introduction to the 2017 Annual Conference of the British Association for South Asian Studies offers an overview of the collection of selected articles presented at the conference. Overall, the Special issue consists of six articles, including four research articles addressing a wide range of topics spanning from the role of women during the Emergency rule (1975–1977) to the difficult relationship between minorities and the Hindu majority in recent years, and two viewpoint articles. These viewpoints touch on two extremely important and timely topics: Urvashi Butalia, who was the keynote speaker at the conference, looks at Partition and at the importance of survivors in preserving the memory of such a momentous event, whereas Deborah Sutton addresses the articulation of Hindu nationalist views in the scholarship of the 'Ghent School'. The introduction to the Special Issue also highlights how the research presented in this collection can offer comparative insights to broader phenomena occurring in other regions alike.